國小教師教學效能自評之研究 A Study of Self-Assessment in Teaching Effectiveness of Elementary School Teachers - 鍾榮進 Jung-Chin Chung (National Changhua University of Education, 2015)
本研究旨在調查國小教師教學效能之現況，並分析不同背景變項對國小教師教學效能之影響。研究採文獻分析、問卷調查與訪談等研究方法。問卷調查以新北市國民小學教師為主要研究對象，計抽取68 所國小、1026 位教師為調查研究對象。並選取國小教師9 人為訪談對象。調查問卷所得資料應用套裝軟體進行分析，另以訪談 作更深入探討。根據研究結果分析與討論，獲以下結論：壹、新北市國小教師教學效能良好，尤其在「教室管理」方面表現最佳， 而在「教學效果」方面得分最低。貳、國小教師之教學效能因不同教師個人背景變項而有差異，其中以女性、年齡較大、教學年資較深、已婚者，其教學效能較高。參、國小教師之教學效能因不同教師個人工作變項而有差異，其中以級任教師、得過優良教師獎勵、任教班級人數較多者，其教學效能較高。肆、國小教師之教學效能因不同學校背景變項而有差異，其中以男性校長、學校規模較大、位於市區之學校教師，其教學效能較高。依據研究所得結論，本研究分別對教師、學校、教育行政機關提出數項建議。 The study aims to investigate the situation of teaching effectiveness of elementary school teachers and to analyze the effects on teaching effectiveness of teachers by different background variables. The study has introduced literature review, questionnaire survey and interview methodologies, in which questionnaire survey targeted elementary school teachers in New Taipei City, totaling 68 research objects via a sampling of 68 elementary schools and 1026 teachers, with 9 elementary school teachers selected as interviewees. Software package was used to conduct analysis based on the data derived from questionnaire survey, with interviews conducted additionally for further discussion. The following conclusions are derived according to analysis and discussion of research outcomes: Elementary school teachers in New Taipei City reported good teaching effectiveness in terms of "classroom management" aspect especially and scored the lowest in terms of "teaching effects" aspect. Teaching effectiveness of elementary school teachers varied by personal background variable of different teachers, in which those older, female, married and with senior length of teaching, reported higher teaching effectiveness. Teaching effectiveness of elementary school teachers varied by personal background variable by different teachers, in which class tutors, those who won the most reward for excellent teacher, in a class with bigger size, reported higher teaching effectiveness. Teaching effectiveness of elementary school teachers varied by different school background variable, in which school teachers who serve in schools with male principal, larger size, located in urban area, reported higher teaching effectiveness. According to the conclusions summarized, the study proposed a few suggestions to teachers, schools, and education administration authority, respectively.